MANAGEMENT SERVER BERBASIS SMS GATEWAY STUDI KASUS PADA GCM EDNOVATION YOGYAKARTA - Hidayatullah, Arif; Wintolo, Hero (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2014)
Trust is a key factor in online communication, a hosting that can be accessed quickly and almost never had an error would indicate that the hosting has managed seriously in serving consumers. Therefore a hosting requires regular maintenance and handling of error as soon as possible before consumers feel the effects. On the other side hosting providers need to protect their systems to provide access to others who don’t have the right and protect it using a firewall. Those two things became very difficult to do simultaneously considering the speed and ease of access contrary to the security of the hosting. There are many ways in which the administrators to handling this case.One of many ways is create a private network that can only be accessed from within the network, during time for treatments this private hosting use SMS as medium, this media have been chosen because it can directly installed within the private network.By using this sms media, administrator can make application that can do the repair server directly without being worried with the danger of the public internet network, because application running on a private network. Applications can also be built more complex so that application will help administrator to monitor condition of the server and repair errors on the server, administrators can do it anywhere without being dependent on a stable internet connection.